Giant bilateral pediatric thymolipoma presenting with respiratory distress - Kanika Sharma; Shilpa Sharma, MCh,PhD; Rachna Seth, MD; Devendra K. Gupta, MCh (Elsevier, 2021)
Thymolipoma is a rare thymic mass usually incidentally diagnosed. We present the case of an 8-year old child who presented with breathlessness and cough. On evaluation, she had a giant anterior mediastinal mass involving bilateral hemithorax (right > left) which was diagnosed as thymolipoma. The child was started on steroids, to which she responded very well initially, but after few months the thymic mass gradually increased again and respiratory distress reccured. Subsequently total excision of mass was done followed by gradually tapering of steroids. The child had excellent recovery and is asymptomatic at 2.5 years follow up.